Firm concentration & job design: The case of schedule flexible work arrangements - Abi Adams; Maria Balgova; Matthias Qian; Tom Waters (Institute for Fiscal Studies (IFS), 2023)
We build a model of job design under monopsony that yields predictions over the relationship between: (i) the amenity value of non-wage job features; (ii) whether they are costly or profitable to firms; (iii) monopsony power. We analyse the amenity value of schedule flexibility offered in the labour market by combining our model's predictions with a new measure of schedule flexibility, which we construct from job vacancy text using a supervised machine learning approach. We show that the amenity value of schedule flexibility depends crucially on whether it is offered alongside a salaried contract that insures workers from earnings variation.
Keywords: 330; Work design; Working time design; Monopsony; Modeling; Arbeitsgestaltung; Arbeitszeitgestaltung; Monopson; Modellierung